Evaluation of Hyperventilation in Treatment of Head Injuries - Crockard, H. A. (1973)
Reduction of the partial pressure of carbon dioxide in the arterial blood by mechanical hyperventilation (Pco(2) 25-30 mm Hg; Po(2) 100-150 mm Hg) may be beneficial in cases of severe head injury. To evaluate its efficacy and establish prognostic guidelines intracranial pressure, radiocirculograms, and cerebrospinal fluid (C.S.F.) lactate levels were studied in 31 patients. In survivors intracranial pressure fell and cerebral blood flow improved with treatment. A C.S.F. lactate greater than 55 mg/100 ml was associated with a poor prognosis. Selection of patients was based on clinical judgement, and adults with signs of extensive brain damage were excluded. The importance of an adequate airway and resuscitation is stressed before a final decision is made. The object of treatment is to improve the quality of survival and the criteria measured may aid in the distinction between patients with a potential for good recovery and those capable only of a vegetative existence. Many associated factors as well as hypocapnia reduce intracranial pressure, and these are discussed. We believe that hyperventilation may improve some head injuries, and further study is indicated.